(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
When it comes to expanding its national grid and electrifying every corner of its land, India, a rapidly growing country, is always trying to do so. Most of India’s energy is produced by large power plants, which are subsequently distributed through a number of grids and networks. India’s energy infrastructure is the best in the world. Electricity dependability is a challenge in some of the most distant or hard-to-reach locations. It is common for power outages to occur in these areas, as well as low supply voltages. It is possible to create clean energy using windmills when the wind blows constantly at an extremely low cut-in speed. Turbines and generators convert the stored wind kinetic energy into electricity in wind farms These facilities create electricity dependent on how fast the winds are blowing at them. As part of the investigation, a windmill was connected to the existing system to generate electricity. There is no need for external battery banks in order for the system to function properly. Once a specific threshold is reached, the windmill will take care of its load, and the extra energy will be sent back into the power grid. Every time the windmill can’t keep up, we’ll have to turn to the grid. Net metering is used for electricity exchange. The model is used to analyze the study’s validity and other technical features. To increase supply dependability, the size of windmills and other grid balancing elements will be adjusted as part of the initiative.